Boy in two views, postmortem daguerreotypes, 1848
Image: Oval 1/9 plate; Two postmortem daguerreotypes of a boy. Preserver: Plain, not embossed. Mat: Oval with sandy finish (late 1840s). Case: Red-velvet covered oval case (Berg No. 6-17a) with push-button fastener.